EVIEW ABOUT THE LEGAL OBLIGATIONS OF THE QUALIFIED ASSISTANT - PEDAGOGUE IN PRIMARY SCHOOL (Annual of the Faculty of Philosophy in Skopje, 2010)
Primary school education is carried out by teachers, qualified assistants (pedagogue, psychologist, sociologist, special education and rehabilitation staff, librarian) and educators. In the paper are presented and analyzed only the up to date legal principles which regulate the status, progress and work responsibility of the qualified assistant - pedagogue in primary school. The analysis shows that in comparison with the previous laws the current Education Law regulates all the important issues concerning the schoolmaster’s work.
Keywords: QUALIFIED ASSISTANT; PEDAGOGUE; PRIMARY SCHOOL; EDUCATION LAW; QUALIFICATIONS OF THE PEDAGOGUE